Boosting antimicrobial activity of ciprofloxacin by functionalization of mesoporous silica nanoparticles - Juan Mora, Blanca de (2021)
Mesoporous silica nanoparticles (MSNs) are very promising nanomaterials for treating bacterial infections when combined with pharmaceutical drugs. Herein, we report the preparation of two nanomaterials based on the immobilization of ciprofloxacin in mesoporous silica nanoparticles, either as the counter-ion of the choline derivative cation (MSN-[Ch][Cip]) or via anchoring on the surface of amino-group modified MSNs via an amide bond (MSN-Cip). Both nanomaterials were characterized by TEM, FTIR and solution 1H NMR spectroscopies, elemental analysis, XRD and N2 adsorption at 77 K in order to provide the desired structures. No cytotoxicity from the prepared mesoporous nanoparticles on 3T3 murine fibroblasts was observed. The antimicrobial activity of the nanomaterials was determined against Gram-positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Klebsiella pneumoniae) bacteria and the results were promising against S. aureus. In the case of B. subtilis, both nanom aterials exhibited higher antimicrobial activity than the precursor [Ch][Cip], and in the case of K. pneumoniae they exhibited higher activity than neutral ciprofloxacin.